Estimating Aedes aegypti (Diptera: Culicidae) Flight Distance: Meta-Data Analysis. Issue 4 (31st May 2022) - Moore, Thomas C; Brown, Heidi E
Abstract: The yellow fever mosquito, Aedes aegypti, is a growing global concern. An ecological parameter necessary for vector control is the dispersal, or flight range, of mosquito vectors. Information on mosquito dispersal supports identifying optimal sampling and control strategies to limit the invasion of adult mosquitoes. Attempts around the world to understand the movement and flight range of Ae. aegypti have used a variety of techniques, but there has been little agreement regarding flight distances of Ae. aegypti, specifically the average linear distance Ae. aegypti travel in their natural environment. To generate a more robust estimate of Ae. aegypti flight distance, we conducted a meta-data analysis with the aims 1) to provide a flight distance measurement and 2) investigate how mosquito flight range can be affected by study design and climatic factors. Published studies were retrieved from public databases and reviewed for mean distance traveled (MDT) or maximum distance traveled measurements of Ae. aegypti . Linear regression was used to assess potential relationships between Ae. aegypti flight distance and factors pertaining to climate, degrees of urbanization, and study design. MDT estimates were pooled from 27 experiments to calculate a weighted MDT of 105.69 m. This study addresses the average flight distance of Ae. aegypti with the intention of informing vector control programs in Ae. aegypti prevalent regions of the world.